2019
DOI: 10.1136/bmjopen-2019-032559
|View full text |Cite
|
Sign up to set email alerts
|

Jandu Yani U ‘For All Families’ Triple P—positive parenting program in remote Australian Aboriginal communities: a study protocol for a community intervention trial

Abstract: IntroductionThe population-based (Lililwan) study of fetal alcohol spectrum disorder (FASD) revealed a high prevalence of FASD in the remote communities of the Fitzroy Valley, Western Australia (WA) and confirmed anecdotal reports from families and teachers that challenging child behaviours were a significant concern. In response, Marninwarntikura Women’s Resource Centre initiated a partnership with researchers from The University of Sydney to bring the positive parenting program (Triple P) to the Valley. Trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In response, a randomised-controlled trial of a culturally appropriate modification of the Alert program was trialled in primary schools to address impulse control and executive functioning [51]. Additionally, a communitymodified, Indigenous Triple-P (positive parenting program) called Jandu Yani U [52] was introduced and shown to increase parents' skills and confidence, decrease challenging behaviours and decrease parental anxiety [53]. This in turn provided data for advocacy and resulted in funding for continuation of the program.…”
Section: Management Of Fasdmentioning
confidence: 99%
“…In response, a randomised-controlled trial of a culturally appropriate modification of the Alert program was trialled in primary schools to address impulse control and executive functioning [51]. Additionally, a communitymodified, Indigenous Triple-P (positive parenting program) called Jandu Yani U [52] was introduced and shown to increase parents' skills and confidence, decrease challenging behaviours and decrease parental anxiety [53]. This in turn provided data for advocacy and resulted in funding for continuation of the program.…”
Section: Management Of Fasdmentioning
confidence: 99%
“…However, participation and retention rates remain a significant challenge for in‐person parent education classes (Bearss et al, 2017; Fleming et al, 2015; Gershy & Omer, 2017). Research has indicated this may be due to parents facing barriers like a lack of universally accessible high‐quality programs, particularly in rural low‐income and ethnic minority areas (Acuña & Martinez, 2018; Andersson et al, 2019). Additionally, they face increasingly limited time to access available services from competing life demands; this is especially salient for families with school‐age children where additional supervision and participation are required (Clarkson & Zierl, 2018; Viola et al, 2020; Walker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, participation and retention rates remain a significant challenge for inperson parent education classes (Bearss et al, 2017;Fleming et al, 2015;Gershy & Omer, 2017). Research has indicated this may be due to parents facing barriers like a lack of universally accessible high-quality programs, particularly in rural low-income and ethnic minority areas (Acuña & Martinez, 2018;Andersson et al, 2019).…”
mentioning
confidence: 99%
“…Triple P, the Positive Parenting Program (Jandu Yani U, meaning ‘For all families’), trained 39 ‘parent coaches’ to assist local families to gain the knowledge and skills required to parent children with emotional and behavioural problems. 20 …”
mentioning
confidence: 99%